Quantum mechanical insights into the properties of graphene-like zinc oxide (g-ZnO) - OREK, Cahit (Academic Press Inc., 2025)
Zinc oxide (ZnO) is a versatile material found in various forms, including bulk, thin films, nanorods, and quantum dots. When thinned down to the atomic level, ZnO undergoes a phase transition from its conventional wurtzite structure to a graphene-like planar configuration (g-ZnO). Standard Density Functional Theory (DFT) methods often prove inadequate for accurately predicting the electronic properties of ZnO. In contrast, the Coulomb-Attenuating B3LYP (CAM-B3LYP) functional has demonstrated the ability to yield results that are in close agreement with experimental values, particularly for band gap predictions, charge-transfer excitations, and optical transitions. This study undertakes a detailed computational investigation of the structural, optical, and electronic properties of graphene-like ZnO (g-ZnO) utilizing the CAM-B3LYP approach. The calculated geometric parameters, electronic band structure, and optical absorption spectra are found to be consistent with existing experimental findings and previous theoretical work. This concordance underscores the efficacy of the CAM-B3LYP functional for modeling low-dimensional semiconductors and provides significant insights into the potential applications of g-ZnO in nanoscale optoelectronics and functional nanomaterials. © 2025
Keywords: CAM-B3LYP functional; Electronic structure calculations; Excited-state absorption analysis; Graphene-like ZnO nanostructures; Low-dimensional semiconductors